Magnitude and determinants for place of postnatal care utilization among mothers who delivered at home in Ethiopia: a multinomial analysis from the 2016 Ethiopian demographic health survey - Brhane Gebrekidan Ayele; Mulugeta Abrha Woldu; Haftom Weldearegay Gebrehiwot; Equbay Gebru Gebre-egziabher; Hailay Gebretnsae; Tsegay Hadgu; Alemnesh Araya Abrha; Araya Abrha Medhanyie (BMC, 2019)
Abstract Introduction Above half of mothers in Ethiopia give birth at home. Home based care within the first week after birth as a complementary strategy to facility-based postnatal care service is critical to increase the survival of both mothers and newborns. However, evidence on utilization of postnatal care and location of service among mothers who delivered at home in Ethiopia is insufficiently documented. Therefore, this study assessed the magnitude and determinants for place of postnatal care service utilization among mothers who delivered at home in Ethiopia. Methods We used the 2016 Ethiopian Demographic and Health Survey, and extracted data from 4491 mothers who delivered at home during 5 years preceding the survey. A multinomial logistic regression model was applied to examine the determinants of both facility and home -based postnatal care service utilization. Likelihood ratio test was used to see the model fitness and p-value of < 0.05 was used to determine statistical significance at 95% confidence interval. Results From the total 4491 mothers who delivered at home, only 130(2.9%) and 236(5.3%) of them utilized postnatal service at home and at a health facility respectively. Being from an urban region (AOR = 0.378, 95%CI: 0.193-0.740), ever using the calendar method to delay pregnancy (AOR = 0.528, 95%CI: 0.337-0.826), receiving four and above antenatal care visits (AOR = 0.245, 95%CI: 0.145-0.413) and having a bank account (AOR = 0.479, 95%CI: 0.243-0.943) were the factors associated with utilizing home- based postnatal care. Similarly being a follower of the orthodox religion (AOR = 1.698, 95%CI: 1.137-2.536), being in the rich wealth index (AOR = 0.608, 95%CI: 0.424-0.873), ever using the calendar method to delay pregnancy (AOR = 0.694, 95%CI: 0.499-0.966), wantedness of the pregnancy (AOR = 0.264, 95%CI: 0.352-0.953), receiving four and above antenatal care visits (AOR = 0.264, 95%CI: 0.184-0.380) and listening to radio at least once a week (AOR = 0.652, 95%CI: 0.432-0.984) were the determinants of facility-based postnatal care utilization. Conclusion The coverage of postnatal care service utilization among mothers who delivered at home was very low. Living in urban region, following the Orthodox religion, having higher wealth index, having a bank account, ever using calendar method to delay pregnancy, wantedness of the pregnancy, receiving four and above antenatal care visit and listening to radio at least weakly were associated with postnatal care service utilization. Therefore, targeted measures to improve socio-economic status, strengthen the continuum of care, and increase health literacy communication are critically important to increase postnatal care service utilization among women who deliver at home in Ethiopia.